Audit Quality With Auditor Ethics as a Moderating Variable - Lestari, Rya Aristia; Djamil, Nasrullah (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study aims to determine the effect of competence, independence, professionalism, work experience, and time budget pressure on audit quality with auditor ethics as a moderating variable. The research method used is quantitative method. The population in this study were all auditors who worked at the Pekanbaru City Public Accounting Firm and the sample was auditors at the Pekanbaru City Public Accounting Firm. The sampling technique in this study uses saturated sampling or often called total sampling (census). The data source used is the main / primary data obtained directly from the questionnaire distributed to respondents. The data analysis method used in this study uses the Partial Least Square (PLS) method to test the six hypotheses proposed in this study. Each hypothesis will be analyzed using SmartPLS 4 software to test the relationship between variables. The results of this study indicate that competence, independence, time budgte pressure have a positive influence on audit quality and auditor ethics can moderate work experience on audit quality. Meanwhile, professionalism and work experience are not proven to have a positive influence on audit quality.